Research on Rehabilitation Training Strategies Using Multimodal Virtual Scene Stimulation - Xie, Ping; Wang, Zihao; Li, Zengyong; Wang, Ying; Wang, Nianwen; Liang, Zhenhu; Wang, Juan; Chen, Xiaoling (Frontiers in Aging Neuroscience, 2022)
It is difficult for stroke patients with flaccid paralysis to receive passive rehabilitation training. Therefore, virtual rehabilitation technology that integrates the motor imagery brain-computer interface and virtual reality technology has been applied to the field of stroke rehabilitation and has evolved into a physical rehabilitation training method. This virtual rehabilitation technology can enhance the initiative and adaptability of patient rehabilitation. To maximize the deep activation of the subject’s motor nerves and accelerate the remodeling mechanism of motor nerve function, this study designed a brain-computer interface rehabilitation training strategy using different virtual scenes. We compared and analyzed the degree of neural activation and the recognition rate of motor imagery in stroke patients after motor imagery training using stimulation of different virtual scenes, which provided the research basis for a virtual rehabilitation strategy that could integrate the motor imagery brain-computer interface and virtual reality technology.